The Development of a Quizizz-Based Summative Assessment Instrument for the IPAS Subject (Science and Social Studies) for Grade IV at SDN 12 Pontianak Kota: PERKEMBANGAN INSTRUMEN ASESMEN SUMATIF BERBASIS QUIZIZZ PADA MATA PELAJARAN IPAS KELAS IV SDN 12 PONTIANAK KOTA - Endah Rizkiani; Hairida Hairida; Rio Pranata (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
This study aims to develop and determine the feasibility level of a Quizizz-based summative assessment instrument for the IPAS subject in Grade IV at SDN 12 Pontianak Kota. The product is designed to help reduce students’ anxiety, boredom, and tension during assessments, as well as to assist teachers in providing prompt feedback. This research employs both quantitative and qualitative approaches using the Research and Development (R&D) method with the ADDIE model. Data were collected through product validation results from subject matter experts, language experts, and media experts, as well as from teacher and student response questionnaires. The results show that the Quizizz-based summative assessment instrument obtained a validity score of 97.91% from subject matter experts, 100% from language experts, and 98.61% from media experts. The response level from teachers was 97.73%, while the student response was 88.97%. Based on these findings, it can be concluded that the Quizizz-based summative assessment instrument for the IPAS subject at SDN 12 Pontianak Kota is feasible for use